2020
DOI: 10.1108/ijrdm-02-2019-0042
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the moderating effect of subjective norm on luxury purchase intention: a study of Gen Y consumers in India

Abstract: PurposeAlthough Generation Y consumers contribute significantly to the luxury market, still there is a limited amount of research conducted to explain their luxury consumption behavior, particularly in context of emerging markets like India. The main objectives of this study are to understand the key factors that affect luxury purchase intentions of Generation Y consumers using the theory of planned behavior (TPB) and to examine the moderating effect of subjective norm on other TPB variables, namely, attitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(135 citation statements)
references
References 89 publications
4
104
0
Order By: Relevance
“…This study aims to bridge this gap. Prior studies have found attitude and subjective norm to be significantly related with luxury purchase intention (Jain, 2020; Summers et al , 2006). Therefore, these variables are chosen as mediators for this study.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This study aims to bridge this gap. Prior studies have found attitude and subjective norm to be significantly related with luxury purchase intention (Jain, 2020; Summers et al , 2006). Therefore, these variables are chosen as mediators for this study.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…They have high disposable income (Deloitte, 2018) and therefore, this group is considered as the major force behind luxury market growth in India. However, very few studies have been conducted to understand Gen Y consumers' luxury purchase behavior in Indian market context (Jain, 2019, 2020). This study tries to bridge this lacuna in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a few studies have considered social influence as a moderator (Sawang et al, 2014; Wan et al, 2018). For example, Jain (2020) argued that, if social influence is favorable to purchase behavior, attitude predictive capability increases. Similarly, Wan et al (2018) suggested that social influence positively moderates the influence of consumers' attitude on their intention to use green space in Hong Kong.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Lately, academic discussions have majorly concentrated on the brand‐new luxury goods (Jain, 2020; Turunen & Leipämaa‐Leskinen, 2015) and have neglected mainly the discussions around rented fashion luxury products. The luxury fashion rental consumption has emerged but is still largely ignored.…”
Section: Introductionmentioning
confidence: 99%